History, status and genetic characteristics of native cattle breeds from the Republic of Kazakhstan - A. K. Khamzina; A. A. Yurchenko; N. S. Yudin; P. Sh. Ibragimov; Y. S. Ussenbekov; D. M. Larkin (Вавиловский журнал генетики и селекции)
This work provides a comprehensive review of the history, status, and genetic characteristics of cattle breeds in Kazakhstan. The current breeding status is analysed, including information on popular breeds such as Kazakh whiteheaded, Auliekol, Alatau, Aulieata, and Kalmyk, their production and economic significance. An overview of genetic studies using DNA fingerprinting, microsatellites, and SNPs aimed at identifying unique characteristics, genetic diversity, and genes under selection, as well as markers of economically important and productive traits of Kazakh cattle breeds, is also provided. The study examined the genetic structure of the Kazakh white-headed and Alatau breeds based on whole-genome SNP genotyping. Unique genetic components characterizing Kazakhstan cattle breeds were described, and comparisons were made with genetic data from other breeds. Structural analysis showed that the Kazakh white-headed breed contains genetic components of the Hereford, Kalmyk, and Altai cattle. The Alatau breed has a composite structure, containing components of the Brown Swiss, Braunvieh, Kalmyk, and Holstein breeds. The results not only reveal the genetic diversity and characteristics of cattle breeds in Kazakhstan and the historical development and current state of animal husbandry in the country, but also emphasize the importance of further research to identify adaptive and unique genetic markers affecting economically important traits of local breeds.